2006
DOI: 10.1002/crat.200610714
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of Dy and La doped SnO2 thin films prepared by a cost effective vapour deposition technique

Abstract: Stannous oxide (SnO 2 ) thin film is one of the most widely used n-type transparent semi-conductor films in electronics, electro-optics and solar energy conversion. By achieving controlled non-stoichiometry, we can get good transparency and high electrical conductivity simultaneously in SnO 2 thin films. Dy and La doped SnO 2 thin films have been prepared by a cost effective vapour deposition technique. The structural, photoelectronic, optical and electrical properties of the doped and undoped films were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The changing of the annealing temperatures from 200 to 800℃ which decreased the density of nucleation centers as shown in Fig. 3 As the temperature increases, a smaller number of unit cells start to grow, which results in large grain size [16]. A smaller crystallite size exhibits larger cell volume and minimum number of unit cells was present.…”
Section: Characterizationmentioning
confidence: 95%
“…The changing of the annealing temperatures from 200 to 800℃ which decreased the density of nucleation centers as shown in Fig. 3 As the temperature increases, a smaller number of unit cells start to grow, which results in large grain size [16]. A smaller crystallite size exhibits larger cell volume and minimum number of unit cells was present.…”
Section: Characterizationmentioning
confidence: 95%
“…Let us emphasize that there are some discrepancies by the RE ion doping. A decrease in for small doping concentrations of different RE ions (for example, Sm, La, Dy, Nd, Eu, Er, and Tb) is also reported in TiO , CeO , or SnO NPs [ 70 , 85 , 90 , 91 , 92 , 93 , 94 ]. However, some authors have observed an increase in the band-gap energy in Sm [ 95 ] and Yb, Sc [ 45 ]-doped TiO NPs, and Pr-doped CeO NPs [ 96 ].…”
Section: Resultsmentioning
confidence: 83%
“…Let us emphasize that there are some discrepancies by the RE ion doping. A decrease in E g for small doping concentrations of different RE ions (for example, Sm, La, Dy, Nd, Eu, Er, and Tb) is also reported in TiO 2 , CeO 2 , or SnO 2 NPs [70,85,[90][91][92][93][94]. However, some authors have observed an increase in the band-gap energy E g in Sm [95] and Yb, Sc [45] It must be mentioned that pure bulk TiO 2 without defects and impurities is diamagnetic due to the presence of Ti 4+ , which has no unpaired electrons, making it diamagnetic.…”
Section: Rare Earth (Sm Tb and Er) Ion Doping Effects On The Band-gap...mentioning
confidence: 68%
“…The degraded field-effect mobility and on-current originated from a significant decrease in the free carrier concentration, originating from the oxygen vacancy in metal oxide semiconductors. In addition, the Y 3+ -Sn 4+ substitution reaction might generate an extra hole carrier, leading to a decrease in free carrier concentration by compensating for electron carrier concentration [26]. In addition, the threshold voltage exhibited a positive shift, in particular, from 0.5 wt% Y.…”
Section: Resultsmentioning
confidence: 99%